Impact of Metronidazole Treatment and Dientamoeba Fragilis Colonization on Gut Microbiota Diversity. Issue 1 (July 2021) - Gotfred-Rasmussen, Helle; Stensvold, Christen Rune; Ingham, Anna Cäcilia; Johannesen, Thor Bech; Andersen, Lee O'Brien; Röser, Dennis; Nielsen, Henrik Vedel
ABSTRACT: Objectives: The intestinal parasite Dientamoeba fragilis is a common colonizer of children in Denmark. Metronidazole has been used to reduce gastrointestinal symptoms in children colonized with D fragilis . We aimed to identify gut microbiota changes associated with D fragilis carrier status and metronidazole treatment of D fragilis -positive children. Methods: The fecal microbiota of 275 fecal samples from children treated with metronidazole (n = 48) or placebo (n = 48) were characterized by ribosomal DNA sequencing. Samples collected before (T1), 2 weeks after (T2), and 8 weeks (T5) after treatment were included. Seventy fecal samples from 70 age-matched parasite-negative children served as controls. Results: The abundance of 24 bacterial genera differed significantly according to D fragilis carrier status, with Flavonifractor being remarkably more abundant in children testing negative for D fragilis . Eight bacterial genera changed significantly in abundance in children losing versus keeping D fragilis after metronidazole treatment. Of these, 7 returned to pretreatment (T1) levels at T5. Meanwhile, the abundance of Flavonifractor continued to differ at T5, whereas for Ruminococcus the abundance only remained high in children who were D fragilis- negative at T2 and T5. Increases in Hungatella, Sutterella, and Streptococcus abundances observed at T2 were specific to metronidazole exposure and hence independent of D fragilis colonization. Conclusions: This study revealed that specific bacterial genera were associated with D fragilis colonization. Metronidazole treatment had a short-term impact on the abundance of some bacterial genera, with most of these reverting to pretreatment levels 8 weeks after completed treatment. Abstract : Supplemental Digital Content is available in the text